Numerical calculation of laminar mixed convection flow of confined square tube banks - See, Kangluo (Nanyang Technological University, 2024)
The aim of this project is to numerically study laminar mixed convection heat transfer and flow around a 2 x 2 array of square cylinders in a square arrangement in a channel (Re = 10 – 50, Ri = -0.5 – 0.5, Pr = 0.7 and 7.0). A finite volume method Python code that is implemented on a collocated grid arrangement is employed to solve the governing equations. The code is second order accurate in space. The systems of equations are solved by the algebraic multigrid method and coupled together using the SIMPLEC algorithm. The code is then validated with other works that studied similar problems. The drag, pressure, friction coefficients are found to increase with increasing Richardson number. The increased/decreased Richardson number is also found to stabilize/destabilize the flow for the same Reynolds number. The temperature field around the square arrays is also presented. It is also found that the Nusselt number increases with increase in Reynolds and Richardson number. Empirical correlations are obtained for the drag coefficient and Nusselt number the range of Reynolds and Richardson numbers studied in this work.